Century of genocide : eyewitness accounts and critical views - Totten, Samuel Hrsg (Garland reference library of social science, 1997)
Which genocide matters more? : learning to care about humanity / Israel W. Charney -- Introduction / Samuel Totten and William S. Parsons -- Genocide of the heroes / Jon Bridgman and Leslie J. Worley -- The Armenian genocide / Rouben P. Adalian -- Soviet man-made famine in Ukraine / James E. Mace -- Soviet deportation of whole nations : a genocidal process / Lyman H. Legters -- Holocause : the Jews / Donald L. Niewyk -- Holocaust : the gypsies / Sybil Milton -- Holocaust : disabled peoples / Hugh Gregory Gallagher -- The Indonesian massacres / Robert Cribb -- Genocide in East Timor / James Dunn -- Genocide in Bangladesh / Rounaq Jahan -- The Burundi genocide / Ren(c)♭ Lemarchand -- The Cambodian genocide-- 1975-1979 / Ben Kiernan -- Physical and cultural genocide of various indigenous peoples / Robert K. Hitchcock and Tara M. Twedt -- The Rwanda genocide / Ren(c)♭ Lemarchand